Hajj and Umra smart mobile Application: Culture and Usability Study - Omar, Firas; Alhmiedat, Tareq; Hassouna, Mohammad (INTERNATIONAL JOURNAL OF COMPUTERS & TECHNOLOGY, 2013)
Mobile technology is becoming more popular around the world. The importance of such technology relates to its capability of allowing the user of performing many different daily basis tasks. Despite the progress made in the mobile application field, there are still some boundaries and limitations in using it. Some of these difficulties are connected directly to the Culture. Other difficulties are related to the experience in using such technology. This research aims to find out the main restrictions and obstacles which limit the use of mobile handsets as an Islamic smart Hajj and Umra Application. The research aim extends to studying the effect of cultural issues on peoples use of the internet on a mobile phone. The research reported here is based on participants from the Hashemite Kingdome of Jordan.